Temporal trends of COVID-19 antibodies in vaccinated healthcare workers undergoing repeated serological sampling: An individual-level analysis within 13 months in the ORCHESTRA cohort - Collatuzzo, Giulia; De Palma, Giuseppe; Violante, Francesco S.; Porru, Stefano; Larese Filon, Francesca; Fabianova, Eleonora; Violán, Concepción; Vimercati, Luigi; Leustean, Mihaela; Rodriguez-Suarez, Marta Maria; Sansone, Emanuele; Sala, Emma; et al. (Frontiers in Immunology, 2023)
Background: Persistence of vaccine immunization is key for COVID-19 prevention. Methods: We investigated the difference between two serological measurement of anti-COVID-19 S1 antibodies in an individual-level analysis on 19,422 vaccinated healthcare workers (HCW) from Italy, Spain, Romania and Slovakia, tested within 13 months from first dose. Differences in serological level were divided by the standard error of the cohort-specific distribution, obtaining standardized measurements. We fitted multivariate linear regression models to identify predictors of difference between two measurements. Results: We observed a progressively reduced difference from <30 days to 210-240 days. Age was associated with increased difference. HCW infected between the two serological measurements had a greater difference compared to the never infected; the infected before the first measurement had a relative risk [RR] of 0.81 for one standard deviation in the difference (95% confidence interval [CI] 0.78-0.85). The RR for a 30-day increase in time between first dose and first serology, and between the two serologies, were 1.08 (95% CI 1.07-1.10) and 1.04 (95% CI 1.03-1.05). The first measurement was a strong predictor of the subsequent antibody decrease (RR 1.60; 95% CI 1.56-1.64). Compared to Comirnaty, Spikevax (RR 0.83, 95% CI=0.75-0.92) and mixed vaccines (RR 0.61; 95% 0.51-0.74) were associated to a smaller decrease. Third vaccine dose was associated with smaller decrease (RR 0.46; 95% CI 0.40-0.54). Conclusions: Age, COVID-19 infection, number of doses, time between first dose and first serology, time between serologies and type of vaccine were associated to difference between two serological measurements within a 13-month period.